2018
DOI: 10.1088/1674-1056/27/6/066501
|View full text |Cite
|
Sign up to set email alerts
|

Phase transition and near-zero thermal expansion of Zr 0.5 Hf 0.5 VPO 7

Abstract: The Zr 0.5 Hf 0.5 VPO 7 is successfully synthesized by the solid-state method with near-zero thermal expansion. Powder x-ray diffraction (XRD), Raman spectroscopy, thermal dilatometry, and scanning electron microscopy (SEM) are used to investigate the structure, the phase transition, and the coefficient of thermal expansion (CTE) of Zr 0.5 Hf 0.5 VPO 7 . The investigation results show that the samples are of the single cubic type with a space group of Pa 3 at room temperature (RT). It can be inferred that the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…[29,30] Similar thermal expansion control behavior occurs in many oxides materials such as NH 3 in ZrW 2 O 8 [31] and Zr 0.5 Hf 0.5 VPO 7 . [32] More recently, Li et al [33] reported that the chemical bond had larger effect on the NTE behavior in MCo(CN)…”
Section: Introductionmentioning
confidence: 99%
“…[29,30] Similar thermal expansion control behavior occurs in many oxides materials such as NH 3 in ZrW 2 O 8 [31] and Zr 0.5 Hf 0.5 VPO 7 . [32] More recently, Li et al [33] reported that the chemical bond had larger effect on the NTE behavior in MCo(CN)…”
Section: Introductionmentioning
confidence: 99%
“…Equation (2) shows that different DAP has a different distance, and the energy of photon emitted is also different. In Eq.…”
Section: -5mentioning
confidence: 99%
“…[1] The negative expansion material has attracted more and more attention due to its special scientific research and application value. At present, the negative expansion materials are the AM 2 O 7 series represented by ZrV 2 O 7 , [2] the series of magnetic materials represented by Mn 3 GaN, [3] the A(CN) 2 series represented by Zn(CN) 2 , [4] the zeolite series represented by siderolite, [5] the two-dimensional graphite as the representative of graphite. [6] In 1997, a rareearth tungstate or molybdate negative thermal expansion material with A 2 M 3 O 12 (A denotes a valence transition metal, M refers to Mo or W) was reported as chemical general formula and negative thermal expansion materials of vanadate series.…”
Section: Introductionmentioning
confidence: 99%
“…To study the crystalline structure in detail and identify the crystalline phase formation, powder XRD is carried out on PANalytical XPert Pro. [29] It is very basic and important characterization technique to determine certain parameters of crystal structure like, crystalline size, lattice constant, bulk density, x-Ray density, stacking fault, lattice strain, micro-strain and dislocation density, and so on. The crystalline phase of the material is confirmed because the obtained XRD pattern consists of very sharp peaks.…”
Section: Xrd Analysismentioning
confidence: 99%